Pi-complexed hollow MOFs (Metal-Organic Frameworks) tubular structure adsorption material as well as preparation method and application thereof
By preparing π complex hollow MOFs tube structure adsorption materials, the existing MOFs are solved instability and single morphology in solution, and efficient adsorption and separation of ethane/ethylene mixed gas is achieved, meeting the industry's demand for diversified morphology.
Patent Information
- Application Number
- CN202411902064.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-23
Smart Images

Figure HDA0005203455140000011 
Figure HDA0005203455140000012 
Figure HDA0005203455140000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of MOFs adsorption materials, and specifically relates to a π-complexed hollow MOFs tube structure adsorption material and a preparation method and application thereof. Background Art
[0002] Metal-Organic Frameworks (MOFs), as an emerging crystalline porous material, have been widely used in the field of adsorption separation due to their advantages such as high specific surface area, adjustable pore environment and pore size. Taking the adsorption separation of ethylene / ethane mixed gas as an example, since ethylene and ethane have similar molecular sizes and similar boiling points, the traditional low-temperature distillation method consumes a lot of energy and has low separation efficiency. The adsorption separation technology using high-performance porous adsorbents is a potential energy-saving separation method to replace traditional low-temperature distillation.
[0003] Adsorbents can be divided into ethane-selective MOFs and ethylene-selective MOFs according to the gas that is preferentially adsorbed. It is difficult to optimize the adsorption and separation performance of ethane-selective MOFs, and the separation efficiency of ethane / ethylene mixed gases is relatively low. Relatively speaking, ethylene-selective MOFs have been favored by many scholars due to their excellent C2H4 / C2H6 IAST separation selectivity. However, ethylene-selective MOFs are mostly unstable in water, acidic or alkaline solutions, and the morphology of the synthesized MOFs adsorbent is relatively simple, which cannot well meet the industrial demand for morphological diversity. Summary of the invention
[0004] The purpose of the present invention is to provide a π-complexed hollow MOFs tube structure adsorption material and its preparation method and application. The obtained MOFs adsorption material has a stable hollow tubular structure and can achieve regulation of microscopic morphology, and exhibits efficient adsorption and separation performance for ethane / ethylene mixed gas.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] Provided is a method for preparing a π-complexed hollow MOFs tube structure adsorption material, comprising the following steps:
[0007] 1) uniformly mixing the metal salt, the organic ligand and the metal ion source in a monohydric alcohol aqueous solution, heating and reacting to obtain the precursor MOFs;
[0008] 2) The precursor MOFs material obtained in step 1) is mixed with a monocarboxylic acid aqueous solution, and etched by a hydrothermal reaction to obtain a π-complexed hollow MOFs tube structure adsorption material.
[0009] According to the above scheme, in step 1), after the reaction is completed, the precursor MOFs are obtained by washing and purification.
[0010] According to the above scheme, in step 2), after the hydrothermal reaction is completed, the reaction is cooled, purified, centrifuged, and dried to obtain a π-complexed hollow MOFs tube structure adsorption material.
[0011] According to the above scheme, in step 1), the reaction temperature is 50-150° C., and the reaction time is 24-48 hours.
[0012] According to the above scheme, in step 1), the metal salt is one of aluminum chloride, ferric chloride, ferric acetate and chromium nitrate.
[0013] According to the above scheme, in step 1), the organic ligand is one of 2-aminoterephthalic acid, 2-hydroxyterephthalic acid, 2-monosodium sulfonateterephthalate and 2-bromoterephthalic acid.
[0014] According to the above scheme, in step 1), the monohydric alcohol is one of methanol, ethanol, propanol and isobutanol. The presence of the monohydric alcohol during the synthesis process can induce MOFs to generate a rod-like structure, and by adjusting the content of the monohydric alcohol in the monohydric alcohol aqueous solution, rod-like structures with different aspect ratios can be obtained, thereby achieving controllable adjustment of their morphology. The more the monohydric alcohol accounts for the volume in the monohydric alcohol aqueous solution, the more slender the morphology of the obtained rod-like structure.
[0015] According to the above scheme, in step 1), the molar ratio of the metal salt to the organic ligand is 1:1.
[0016] According to the above scheme, in step 1), the molar volume ratio of the metal salt to the monohydric alcohol is 1 mmol: 1-20 mL.
[0017] According to the above scheme, in step 1), the volume ratio of water to monohydric alcohol in the monohydric alcohol aqueous solution is 1 to 10:1.
[0018] According to the above scheme, in step 1), the metal ion in the metal ion source is one of Cu(I), Ag(I), Pt(II) and Pd(II). Preferably, the metal ion source is cuprous chloride, silver tetrafluoroborate, potassium tetrachloroplatinate and palladium chloride.
[0019] According to the above scheme, in step 1), the molar ratio of metal salt to metal ion is 1:0.1-2; wherein the mass of metal ions loaded on the adsorption material accounts for 1-20wt% of the mass of metal ion feed.
[0020] According to the above scheme, in step 2), the mass volume ratio of the precursor MOFs material to the monocarboxylic acid aqueous solution is 100 mg: 5-15 mL.
[0021] According to the above scheme, in the step 2), the volume ratio of monocarboxylic acid to water in the monocarboxylic acid aqueous solution is 6:1 to 16. The presence of water during the etching process accelerates the nucleation of MOFs, resulting in more internal defects. As the reaction proceeds, the metal salt and organic ligand are consumed in large quantities, the concentration of the reactants continues to decrease, the growth rate of MOFs slows down, and the external defects are less. The monocarboxylic acid preferentially etches the part with more defects, so that a hollow MOFs tube structure material can be obtained.
[0022] According to the above scheme, in step 2), the organic monocarboxylic acid used in the monocarboxylic acid aqueous solution is one of formic acid, acetic acid, propionic acid, butyric acid and lauric acid.
[0023] According to the above scheme, in step 2), the hydrothermal reaction conditions are: 100-120° C., constant temperature reaction for 3-12 hours.
[0024] Provided is a π-complexed hollow MOFs tube structure adsorption material prepared by the above-mentioned preparation method, wherein the inner diameter of the hollow MOFs tube is 0.3-6 μm and the length is 1-100 μm.
[0025] Provided is an application of a π-complexed hollow MOFs tube structure adsorption material prepared by the preparation method in ethane / ethylene gas adsorption separation.
[0026] According to the above scheme, the use conditions of the adsorbent in adsorption separation are: temperature of 0 to 40°C; and pressure of 0 to 1 bar.
[0027] Beneficial effects of the present invention:
[0028] 1. The present invention provides a method for preparing a π-complexed hollow MOFs tube structure adsorbent material. In the process of preparing precursor MOFs, the presence of monohydric alcohol can induce MOFs to generate a rod-like structure, and by adjusting the content of monohydric alcohol in a monohydric alcohol aqueous solution, rod-like structures with different aspect ratios are obtained, thereby achieving controllable adjustment of the morphology; the precursor MOFs are then etched with a monocarboxylic acid aqueous solution to obtain a hollow MOFs tube morphology; the obtained stable hollow structure not only improves the mass transfer rate of gas molecules in the adsorbent, which is beneficial to the rapid anchoring of gas molecules by the adsorbent, but also provides more exposure sites for metal ions introduced into the adsorbent, synergistically enhancing and improving the π-complexation reaction of ethylene molecules and metal ions; thereby achieving efficient adsorption and separation of ethane / ethylene, and having important application prospects.
[0029] 2. The preparation process of the present invention is simple, the aspect ratio of the obtained hollow MOFs tube structure adsorption material is controllable and adjustable, and the adjustability of the morphology can meet various industrial application requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1The SEM images of the adsorbent materials of the π-complexed hollow MOFs tube structure and the schematic diagram of the inner diameter of the tube are shown in Examples 1 and 2 of the present invention. The water-to-alcohol ratio of (a) and (b) is 30 mL:3 mL, and the water-to-alcohol ratio of (c) and (d) is 30 mL:6 mL.
[0031] Figure 2 This is the N2 adsorption-desorption isotherm of the adsorption material of the π-complexed hollow MOFs tube structure described in Examples 3 and 4 of the present invention. Pressure: 0-1 bar.
[0032] Figure 3 This is the XRD diagram of the adsorption material of the π-complexed hollow MOFs tube structure described in Example 3 of the present invention.
[0033] Figure 4 This is a SEM image of the adsorbent material A described in Comparative Example 1 of the present invention.
[0034] Figure 5 The single component adsorption isotherms of ethane and ethylene tested at 298 K for the MOFs adsorbent materials prepared in Example 5 of the present invention and Comparative Example 1. Pressure: 0-1 bar.
[0035] Figure 6 This is a graph showing the cyclic adsorption test of ethylene by the adsorption material of the π-complexed hollow MOFs tube structure described in Example 5 of the present invention at 298 K. Pressure: 0-1 bar. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with examples and drawings. These examples are merely descriptions of preferred implementations of the present invention, but are not limited to the contents described below.
[0037] Example 1
[0038] Provided is a method for preparing a π-complexed hollow MOFs tube structure adsorption material, comprising the following steps:
[0039] 181 mg 2-aminoterephthalic acid, 40 mg silver tetrafluoroborate, 162 mg ferric chloride, 3 mL ethanol and 30 mL water were added to a round-bottom flask and ultrasonicated for 10 min at room temperature. The mixture was placed in an oil bath, reacted at 110 ° C for 24 h, then taken out and vacuum dried at 80 ° C overnight to obtain the precursor MOFs.
[0040] 100 mg of precursor MOFs was added to 10 mL of acetic acid / water (6:10, v:v) mixed solution, and ultrasonicated for 5 min to make the MOFs evenly dispersed. Then the solution was placed in an oven at 100 °C and etched by hydrothermal reaction for 12 h. After vacuum drying at 80 °C for 10 h, the π-complexed hollow MOFs tube structure adsorption material was obtained, which was recorded as Ag(I)@H-MIL-101-NH2-3 mL.
[0041] Example 2
[0042] The steps were basically the same as those in Example 1, except that the volume of ethanol added was changed to 6 mL, recorded as Ag(I)@H-MIL-101-NH2-6 mL.
[0043] The SEM images of the Ag(I)@H-MIL-101-NH2-3mL material prepared in Example 1 and the Ag(I)@H-MIL-101-NH2-6mL material prepared in Example 2 are shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the microstructure of the prepared adsorbent material presents a hollow tubular structure. Figure 1 It can be seen from (a) and (c) that when the ratio of water to alcohol changes from 30mL:3mL to 30mL:6mL, the tube structure of the hollow tube becomes more slender. Among them, by comparing the tube diameter of any adsorbent material obtained with the ruler in the lower right corner of the SEM scan image, it can be estimated that the inner diameters of Ag(I)@H-MIL-101-NH2-3mL and Ag(I)@H-MIL-101-NH2-6mL are 1μm and 2μm, respectively, and the length is 1 to 30μm.
[0044] Example 3
[0045] Provided is a method for preparing a π-complexed hollow MOFs tube structure adsorption material, comprising the following steps:
[0046] 181 mg 2-aminoterephthalic acid, 40 mg silver tetrafluoroborate, 133 mg aluminum chloride, 6 mL ethanol and 30 mL water were added to a round-bottom flask and ultrasonicated for 10 min at room temperature. The mixed solution was placed in an oil bath, reacted at 110 ° C for 24 h, then taken out and vacuum dried at 80 ° C overnight to obtain the precursor MOFs.
[0047] 100 mg of precursor MOFs was added to 10 mL of acetic acid / water (6:10, v:v) mixed solution, and ultrasonic treatment was performed for 5 min to make the MOFs evenly dispersed. Then the solution was placed in an oven at 100 °C for hydrothermal etching for 12 h, and vacuum dried at 80 °C for 10 h to obtain the π-complexed hollow MOFs tube structure adsorption material, which was recorded as Ag(I)@H-MIL-101-NH2.
[0048] The XRD pattern of the Ag(I)@H-MIL-101-NH2 material prepared in this example is shown in Figure 3 As shown, it can be seen from the figure that the characteristic peaks of the adsorbent material synthesized by the method of the present invention are in good agreement with the standard peaks, which indicates the successful synthesis of the adsorbent. It also shows that the adsorbent material has high phase purity and stable chemical structure.
[0049] Example 4
[0050] The steps were basically the same as those in Example 3, except that the added silver tetrafluoroborate was replaced with an equimolar amount of cuprous chloride, and the obtained material was recorded as Cu(I)@H-MIL-101-NH2.
[0051] The N2 isotherms of the Ag(I)@H-MIL-101-NH2 material prepared in Example 3 and the Cu(I)@H-MIL-101-NH2 material prepared in Example 4 were measured by a Bester adsorption analyzer (Beijing) in a constant temperature liquid nitrogen bath at 77K. The N2 adsorption-desorption curves are shown in Figure 2 As shown, it can be seen that the curve has a large hysteresis loop, indicating the existence of hollow structures of the two materials, which explains the successful etching of the rod-shaped material using a monocarboxylic acid aqueous solution, indicating that the inventive method can successfully synthesize adsorbents with hollow tube structures. The specific surface areas of Ag(I)@H-MIL-101-NH2 adsorbent and Cu(I)@H-MIL-101-NH2 adsorbent calculated by the BET equation are 398m 2 / g and 340m 2 / g. By comparing the specific surface areas of the two adsorbents, we can see that the difference is not obvious, indicating that changing the type of introduced metal ions has little effect on the specific surface area of the adsorbent material. Therefore, we should choose the metal ions with the best separation performance of the optimized adsorbent material, so as to improve and enhance the adsorption and separation effect of the required adsorbent on ethane / ethylene mixed gas.
[0052] Example 5
[0053] Provided is a method for preparing a π-complexed hollow MOFs tube structure adsorption material, comprising the following steps:
[0054] Add 268 mg of monosodium 2-sulfonate terephthalate, 40 mg of silver tetrafluoroborate, 162 mg of ferric chloride, 6 mL of ethanol and 30 mL of water to a round-bottom flask and ultrasonicate for 10 min at room temperature. Put the mixed solution into an oil bath, react at 110 ° C for 24 hours, take it out, and vacuum dry it at 80 ° C overnight to obtain the precursor MOFs.
[0055] 100 mg of precursor MOFs was added to 10 mL of acetic acid / water (6:10, v:v) mixed solution, and ultrasonic treatment was performed for 5 min to evenly disperse the MOFs. The solution was then placed in an oven at 100 °C for hydrothermal etching for 12 h, and vacuum dried at 80 °C for 10 h to obtain the π-complexed hollow MOFs tube structure adsorption material, which was recorded as Ag(I)@H-MIL-101-SO3.
[0056] Comparative Example 1
[0057] In this comparative example, the following methods were used to prepare adsorption material A (Ag(I)@MIL-101-SO3) and adsorption material B (H-MIL-101-SO3), and the adsorption and separation performance of different materials was investigated.
[0058] (1) Preparation of adsorption materials:
[0059] Adsorption material A: 268 mg of monosodium 2-sulfonate terephthalate, 40 mg of silver tetrafluoroborate, 162 mg of ferric chloride, 23 mL of DMF and 1 mL of acetic acid were added to a round-bottom flask, and the mixture was ultrasonicated for 10 min at room temperature. The mixture was placed in an oil bath, reacted at 110 ° C for 24 h, then taken out and vacuum dried at 80 ° C for 10 h to obtain the π-complexed MOFs adsorption material, recorded as Ag(I)@MIL-101-SO3.
[0060] Adsorbent material B: 268 mg of monosodium 2-sulfonate terephthalate, 162 mg of ferric chloride, 23 mL of DMF and 1 mL of acetic acid were added to a round-bottom flask, and the mixture was ultrasonicated for 10 min at room temperature. The mixture was placed in an oil bath, reacted at 110 ° C for 24 h, and then taken out and vacuum dried at 80 ° C overnight to obtain precursor MOFs. 100 mg of precursor MOFs was added to 10 mL of acetic acid / water (6:10, v:v) mixed solution, ultrasonicated for 5 min to make the MOFs dispersed evenly, placed in an oven at 100 ° C for etching for 12 h, and vacuum dried at 80 ° C for 10 h to obtain the hollow MOFs adsorbent material, which was recorded as H-MIL-101-SO3.
[0061] (2) Characterization:
[0062] The morphology and structure of adsorbent material A were characterized by SEM testing method. Figure 4 As shown, the adsorbent material presents a regular octahedral structure. Figure 1 and Figure 4 It can be found that the presence of monohydric alcohol in the material preparation process can indeed induce the MIL-101 series adsorbents to form a rod-like structure morphology.
[0063] (3) Ethane / ethylene adsorption separation performance test:
[0064] The adsorbent material was degassed at 150°C under vacuum for 10 h to obtain an activated adsorbent. Using a Bester adsorption analyzer (Beijing), single-component adsorption tests of ethane and ethylene were performed on Ag(I)@H-MIL-101-SO3, adsorbent material A and adsorbent material B at 298K and 1 bar, and single-component adsorption isotherms of different samples were obtained.
[0065] like Figure 5 As shown, the adsorption amounts of ethylene and ethane by the π-complexed hollow MOFs tube structure adsorbent Ag(I)@H-MIL-101-SO3 in Example 3 are 2.62mmol / g and 1.22mmol / g, respectively, for adsorbent A is 2.64mmol / g and 1.83mmol / g, and for adsorbent B is 1.99mmol / g and 1.62mmol / g. The single-component adsorption isotherms of ethane and ethylene of the first two adsorbent materials were fitted using the Dual-Site Langmuir (DSL) equation, and the Langmuir-Freundlich (LF) equation was fitted for adsorbent B. The C2H4 / C2H6 IAST of Ag(I)@H-MIL-101-SO3, Ag(I)@MIL-101-SO3 and H-MIL-101-SO3 were calculated to be 11.95, 3.44, and 1.37, respectively.
[0066] Compared with adsorbent material B, the adsorbent Ag(I)@H-MIL-101-SO3 obtained by introducing metal Ag(I) into the adsorbent material has a significantly improved adsorption capacity for ethylene, resulting in a significant increase in the C2H4 / C2H6 IAST selectivity of Ag(I)@H-MIL-101-SO3 by nearly 9 times, indicating that the active site metal ions introduced into the adsorbent have a strong π complex reaction with ethylene molecules. Similarly, compared with adsorbent material A, the selectivity of the hollow structure adsorbent Ag(I)@H-MIL-101-SO3 obtained after etching with a monocarboxylic acid aqueous solution has also increased by nearly 3.5 times, indicating that the hollow tube structure material described in the present invention can significantly improve the material's adsorption capacity for ethylene molecules, thereby significantly improving the C2H4 / C2H6 IAST separation selectivity of the adsorbent. In summary, the π-complexed hollow MOFs tube structure adsorbent material obtained by introducing metal ion active sites into the adsorbent material and etching with a monocarboxylic acid aqueous solution can preferentially adsorb ethylene molecules in ethane / ethylene mixed gas and exhibit a high ethylene adsorption capacity. In addition, the adsorbent material prepared by the present invention has an advantageous C2H4 / C2H6 IAST separation selectivity, can achieve efficient separation in ethane / ethylene mixed gas, and is expected to become an alternative adsorbent for separating mixed gases using traditional methods in industry.
[0067] (4) Stability performance test:
[0068] After testing the separation performance of the adsorbent Ag(I)@H-MIL-101-SO3, we further studied its stability. Using a Bester adsorption analyzer (Beijing), we conducted five ethylene adsorption-desorption cycle tests at 298K and 1 bar. The results are as follows: Figure 6 After 5 adsorption cycles, the adsorption capacity of the adsorbent for ethylene did not decrease significantly, indicating that the adsorbent prepared by the method of the present invention always maintains a stable chemical structure and pore structure during the adsorption process, and has obvious advantages over other adsorbent materials.
[0069] It must be emphasized that the above examples are only examples for clearly illustrating the present invention, and are not a complete limitation of the implementation methods. Ordinary technicians in the relevant field can also make other different forms of changes based on the above description. It is impossible and unnecessary to give examples for all the implementation methods here, but the obvious changes derived therefrom still fall within the scope of protection of the present invention.
Claims
1. A method for preparing a π-complexed hollow MOFs tube structure adsorption material, characterized in that: The following steps are involved: 1) uniformly mixing the metal salt, the organic ligand and the metal ion source in a monohydric alcohol aqueous solution, heating and reacting to obtain the precursor MOFs; 2) The precursor MOFs material obtained in step 1) is mixed with a monocarboxylic acid aqueous solution, and etched by a hydrothermal reaction to obtain a π-complexed hollow MOFs tube structure adsorption material.
2. The preparation method according to claim 1, characterized in that: In the step 1), the reaction temperature is 50-150° C. and the reaction time is 24-48 hours.
3. The preparation method according to claim 1, characterized in that: In the step 1), the metal salt is one of aluminum chloride, ferric chloride, ferric acetate and chromium nitrate; the organic ligand is one of 2-aminoterephthalic acid, 2-hydroxyterephthalic acid, 2-sodium sulfonate terephthalate and 2-bromoterephthalic acid; and the metal ion in the metal ion source is one of Cu(I), Ag(I), Pt(II) and Pd(II).
4. The preparation method according to claim 1, characterized in that: In the step 1), the monohydric alcohol is one of methanol, ethanol, propanol and isobutanol.
5. The preparation method according to claim 1, characterized in that: In the step 1), the molar ratio of the metal salt to the organic ligand is 1:1; the molar ratio of the metal salt to the metal ion source is 1:0.1-2.
6. The preparation method according to claim 1, characterized in that: In the step 1), the molar volume ratio of the metal salt to the monohydric alcohol is 1 mmol:1-20 mL; in the monohydric alcohol aqueous solution, the volume ratio of water to the monohydric alcohol is 1-10:
1.
7. The preparation method according to claim 1, characterized in that: In the step 2), in the monocarboxylic acid aqueous solution, the volume ratio of the monocarboxylic acid to water is 6:1-16; wherein the monocarboxylic acid is one of formic acid, acetic acid, propionic acid, butyric acid and lauric acid.
8. The preparation method according to claim 1, characterized in that: In the step 2), the hydrothermal reaction conditions are: 100-120° C., constant temperature reaction for 3-12 hours.
9. A π-complexed hollow MOFs tube structure adsorption material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: In the π-complexed hollow MOFs tube structure adsorption material, the inner diameter of the hollow MOFs tube is 0.3 to 6 μm, and the length is 1 to 100 μm.
10. Use of the π-complexed hollow MOFs tube structure adsorption material as claimed in claim 9 in ethane / ethylene gas adsorption separation.
Citation Information
Patent Citations
C2H3N@Ni(2-MTPA)(TED)0.5 material capable of adsorbing ethane preferentially, and preparation method thereof
CN106622150A
Method for preparing multi-shell hollow structure metal organic framework material
CN107434815A
Metal organic frame material for separating ethane and ethylene and separation method of ethylene and ethane
CN108014752A
MOFs adsorbent for selectively adsorbing esters as well as preparation method and application of MOFs adsorbent
CN111203188A
Acid etching three-dimensional fold type hollow MOF catalyst as well as preparation method and application thereof
CN112191274A